Self-confidence as a mediator between physical fitness and academic achievement: A review of the literature - Saraswara, Bella Shasi; Maksum, Ali; Priambodo, Anung; Kusnanik, Nining Widyah; Turi, Moh (Edelweiss Applied Science and Technology, 2025)
The primary aim of this literature review was to analyze the influence of physical fitness and self-confidence on adolescent academic achievement through several pathways, including improved cognition, focus, and memory. This literature review was conducted using the Preferred Reporting Items for Systematic Literature Reviews (SLR) guidelines. The search continued to PUBMED and Google Scholar through the Publish or Perish (PoP) application. Once the analysis was completed, 41 articles met the requirements. Research shows that there is a positive relationship between physical activity levels (especially moderate to strenuous physical activity) and fitness components (such as muscle strength, speed-agility, and cardiorespiratory fitness) with self-esteem and interpersonal relationships in adolescents. The research used was a correlational design, which involved observing a group of participants at a single point in time. The findings of this literature review are that physical fitness and self-confidence have a positive influence on adolescents’ academic achievement. Practical implications include improving fitness programs in schools, which involve sports and physical exercise to support adolescents’ physical and academic well-being, focusing on boosting confidence and supporting academic achievement. More research is needed to understand other factors such as sleep, diet, and stress management that affect academic performance with the right policies.